Mass production, formulation and delivery of metarhizium anisopliae var. anisopliae for control of sunterranean termite coptotermes curvignathus holmgren (Isoptera: Rhinotermitidae) in oil palm on peat - Nyam, Vei Ting (2015)
The termite Coptotermes curvignathusis a very important pest of oil palm in peat. Conventional methods such as using spraying chemical pesticide and physical barrier do not provide long term control. An alternative method by using entomopathogenic fungus has great potential as a biopesticide against the termite. However, in order to effectively use entomopathogenic fungus to control the subterranean termite, the fungus quality in terms of the ability cause epizootic to termite, method of delivery and application in field are the main concern to researcher. In this study, liquid state fermentation was used to increase the fungus quality and to obtain large quantity in shorter time. Three different types of liquid mediums which were Jenkins medium, Leland medium and MPOB medium were used to mass a produce pathogenic local isolate of Metarhizium anisopliae var. anisopliae. Fungus in Jenkins medium yielded significantly highest number of submerged conidia with 2.36 x 109 submerged conidia/mL even in lowest growth rate on day 3 after inoculation. Fungus culture from Jenkins medium with concentration of 1:0 fungus culture to distilled water showed ability to cause 100% mortality in day 4 after treatment compared to MPOB medium in day 6 after treatment and Leland medium in day 9 after treatment. The fungus was then incorporated with 8 different combinations of bait matrix to formulate into a bait which can attract termite, reduce repellence, prolong active ingredient (fungus) shelf life, and sustain the ability to control termite colony. From the choice feeding test, bait matrix made of dextrin, PVP K90 and skim milk (DPS) impregnated with the fungus has the ability to attract termite compared to other bait matrix. Furthermore, DPS bait has ability to cause 100% mortality on 19 days after treatment. Termite took shorter time to finish the DPS bait with 11.2 day to consume all the baits, and consumed significantly larger quantity of DPS bait compared to the 7 other baits which consisted of different proportion of skim milk, dextrin, PVP K90 and kaolin. Shelf life of the baits were tested through bioassays. All baits were able to maintain consistent termite mortality of more than 80% for over 6 months. A specially designed bait delivery system was adapted to local peat environment was developed to deliver the selected baits DPS and PS infested oil palm tree in the field. Over the 6 months trial period, bait designed delivery system was able to protect the bait from getting wet by rain water and the high water table in peat soil. Termites were found colonizing the PVP K90 plus skim milk (PS) bait chamber as early as one week after application. Termites collected from the vicinity of the bait chamber were found infected and killed by M. anisopliae. There were no C. curvignathus found in the previously infested palm trees at the end of the trial period. The formulated bait delivered in termite baiting system had shown effectiveness in the control of termite in oil palm plantation in peat soil area.